2009
DOI: 10.1177/0738894209343887
|View full text |Cite
|
Sign up to set email alerts
|

Trading Data

Abstract: Some scholars have rushed to judgment about the nature of the relationship between trade and conflict, making strong assumptions about the data upon which their conclusions rest. In this paper, we test these assumptions, showing that they are often not warranted and, thus, pose threats to many of our conclusions about trade's impact on conflict. We discuss official trade statistics; the treatment of missing trade data; and problems with some decision rules being adopted within our research community. We introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The dataset consists of trade flows between states for the years 1870-2009 (v3.0) and is publicly available from the Correlates of War website at http://www.correlatesofwar.org/ [22,23]. We focused on the dyadic trade network, where each link represents the trade flow between pairs of states in current U.S. dollars.…”
Section: Fig 6: Sociopatterns Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The dataset consists of trade flows between states for the years 1870-2009 (v3.0) and is publicly available from the Correlates of War website at http://www.correlatesofwar.org/ [22,23]. We focused on the dyadic trade network, where each link represents the trade flow between pairs of states in current U.S. dollars.…”
Section: Fig 6: Sociopatterns Datamentioning
confidence: 99%
“…The second real network we consider is the financial trade network over the period 1870-2009 [22,23]. The original dataset is weighted and directed.…”
Section: B International Trade Networkmentioning
confidence: 99%
“…With it, we have confirmed that the outcomes correspond to stable configurations in a broad range of the control parameters, in good agreement with the analytical results. Moreover, as a first step towards more realistic cases, we have applied our model to the study of the coalitions during the Cold War using real data obtained from The Correlates of War Project (COW) [55].…”
Section: Discussionmentioning
confidence: 99%
“…To estimate US influence in the region we use trade data provided by Barbieri, Keshk, and Pollins (2009). We compute total trade as the sum of exports and imports to the US and then divide it by population to get a per capita specification that controls for country size.…”
Section: System-level Variablesmentioning
confidence: 99%